Gastrointestinal protective efficacy of Kolaviron (a bi‑flavonoid from Garcinia kola) following a single administration of sodium arsenite in rats: Biochemical and histopathological studies (2015)
Background: Arsenic intoxication is known to produce symptoms including diarrhea and vomiting, which are indications of gastrointestinal dysfunction. Objective: We investigated whether Kolaviron (KV) administration protected against sodium arsenite (NaAsO2)-induced damage to gastric and intestinal epithelium in rats. Materials and Methods: Control rats (Group I) were given a daily oral dose of corn oil. Rats in other groups were given a single dose of NaAsO2 (100 mg/kg; intraperitoneal) alone (Group II) or after pretreatment for 7 days with KV at 100 mg/kg (Group III) and 200 mg/kg (Group IV). Rats were sacrificed afterward and portions of the stomach, small intestine and colon were processed for histopathological examination. Hydrogen peroxide, reduced glutathione, malondialdehyde (MDA) concentrations as well as activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione S transferase (GST) and myeloperoxidase (MPO) were measured in the remaining portions of the different gastrointestinal tract (GIT) segments. Results: NaAsO2 caused significant increases (P < 0.05) in MDA levels and MPO activity, with significant reductions (P < 0.05) in GST, GPX, CAT and SOD activities in the stomach and intestines. KV significantly reversed the changes (P < 0.05) in a largely dose-dependent manner. The different segments had marked inflammatory cellular infiltration, with hyperplasia of the crypts, which occurred to much lesser degrees with KV administration. Conclusion: The present findings showed that KV might be a potent product for mitigating NaAsO2 toxicity in the GIT.